SPARING SURGERY IN A PATIENT OF REPRODUCTIVE AGE WITH CERVICAL PREGNANCY (clinical observation) - I. O. Makarov; G. L. Ermolenko; N. M. Hayrudinova (Акушерство, гинекология и репродукция, 2016)
The authors describe a case study of cervical pregnancy with organsparing surgical treatment in a 35 years woman.